Towards the Knowledge and Innovation System for the Bioeconomy? - Giacomo Maria Rinaldi; Davide Viaggi (Bio-based and Applied Economics)
The bioeconomy is a growing sector in both high- and low-income countries, closely linked to innovation. However, knowledge creation and innovation flows remain underexplored due to their complexity. This study aims to introduce the Knowledge and Innovation System for the Bioeconomy (KISB) to analyze sector dynamics. A systematic literature review examined its application, revealing the need for both technology- and collaboration-focused approaches. Key findings emphasize the importance of multi-actor and multidisciplinary strategies, with recent research prioritizing collaboration over innovation. Ethical and market challenges were noted in commercialization. Additionally, the concept of microKISB, operating at an organizational level, offers potential in business and policy research. Ultimately, KISB and microKISB serve as tools for policymakers, businesses, and researchers to drive bioeconomy advancements.